The Italian Standardization of the Cerebellar Cognitive Affective/Schmahmann Syndrome Scale: Cognitive Profiling in a Healthy, Heterogeneous Population - Maria Devita; Adele Ravelli; Anna Panzeri; Anna Castaldo; Maria Arioli; Giusi Olivito; Angela Berardi; Alessandro Miscioscia; Chiara Ferrari; Libera Siciliano; Caterina Mariotti; Marina De Rui; et al. (The Cerebellum, 2025)

Prevalence of perfluoroalkyl substances in paired batches of precooked and canned bovine meat and their implication on consumer safety - Maria Nobile; Sara Panseri; Dalia Curci; Luca Maria Chiesa; Sergio Ghidini; Francesco Arioli (Food and Chemical Toxicology, 2024)

Occurrence of perfluoroalkyl substances in canned tuna and their impact on food safety - Maria Nobile; Luca Maria Chiesa; Roberto Edoardo Villa; Luigi Danesi; Francesco Arioli; Sara Panseri (Food Control, 2024)

Bio-based packaging combined to protective atmosphere to manage shelf life of salami to enhance food safety and product quality - Maria Nobile; Luca Maria Chiesa; Francesco Arioli; Sara Panseri (Meat Science, 2024)

Canine amniotic fluid at birth: From a discarded sample to a potential diagnostic of neonatal maturity - Federica Riva; Joel Filipe; Radmila Pavlovic; Alberto Maria Luciano; Paola Dall’Ara; Francesco Arioli; Alessandro Pecile; Debora Groppetti (Animal Reproduction Science, 2023)

Trends and potential human health risk of trace elements accumulated in transplanted blue mussels during restoration activities of Flekkefjord fjord (Southern Norway) - Marco Parolini; Sara Panseri; Federico Håland Gaeta; Luciana Rossi; Matteo Dell’Anno; Federica Ceriani; Beatrice De Felice; Trond Rafoss; Francesco Arioli; Salvatore Pilu; Luca Maria Chiesa (Environmental Monitoring and Assessment, 2022)
The monitoring of contaminants represents a priority to preserve the integrity of marine ecosystems, as well as to plan and to manage restoration activities in order to protect environmental and human health. In the present study, a 6-months active biomonitoring was performed to explore the levels of eighteen trace and toxic elements, including heavy metals (TEs; i.e. Al, As, Ca, Cd, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Ni, P, Pb, Sr, Ti, and Zn), accumulated in soft tissues of blue mussel ( Mytilus edulis Linnaeus, 1758) individuals transplanted at different depths (5- and 15-m depth) in five locations within the Flekkefjord fjord (Southern Norway). As this area suffered a long-lasting contamination due to both organic and inorganic contaminants, a series of restoration activities were activated to tackle and to prevent potential risks for ecosystem and local population. Our results demonstrated that the levels of TEs accumulated in edible tissues of transplanted mussels in the Flekkefjord fjord were generally low before the beginning of the restoration activities. However, location- and time-specific differences in the accumulation of TEs were noted after the implementation of such activities. Interestingly, the levels of Fe and Mn significantly increased after the beginning of the restoration activities, likely because the release of these TEs from the slag used in such operations and/or resuspension of contaminated sediments. However, assuming that native mussels can accumulate the same TEs at levels measured in transplanted individuals, our results suggest a substantial safety for human consumption of native mussels from the Flekkefjord fjord, regardless of restoration activities.

Neural representation of social concepts: a coordinate-based meta-analysis of fMRI studies - Maria Arioli; Claudia Gianelli; Nicola Canessa (Brain Imaging and Behavior, 2021)

Incidence of persistent contaminants through blue mussels biomonitoring from Flekkefjord fjord and their relevance to food safety - Marco Parolini; Sara Panseri; Federico Håland Gaeta; Federica Ceriani; Beatrice De Felice; Maria Nobile; Trond Rafoss; Jeff Schnell; Isaline Herrada; Francesco Arioli; Luca Maria Chiesa (Food Additives & Contaminants: Part A, 2020)

An Italian survey of undeclared allergens in food over the years 2014–2018 - Lucia DeCastelli; Francesco Arioli; Daniela Manila Bianchi; Antonio Barbaro; Maria Nobile; Sara Panseri; Luca Maria Chiesa (Food Additives & Contaminants Part B-Surveillance, 2020)

Presence of emerging contaminants in baby food - Maria Nobile; Francesco Arioli; Radmila Pavlovic; Federica Ceriani; Shih-Kuo Lin; Sara Panseri; Roberto Villa; Luca Maria Chiesa (Food Additives & Contaminants: Part A, 2020)

Presence of organic halogenated compounds, organophosphorus insecticides and polycyclic aromatic hydrocarbons in meat of different game animal species from an Italian subalpine area - Francesco Arioli; Federica Ceriani; Maria Nobile; Roberto Vigano'; Martina Besozzi; Sara Panseri; Luca Maria Chiesa (Food Additives & Contaminants: Part A, 2019)

Exposure to metals and arsenic from yellow and red tuna consumption - Luca Maria Chiesa; Federica Ceriani; Antonio Procopio; Sonia Bonacci; Renato Malandra; Sara Panseri; Francesco Arioli (Food Additives & Contaminants: Part A, 2019)

Food risk characterization from exposure to persistent organic pollutants and metals contaminating eels from an Italian lake - Luca Maria Chiesa; Emanuela Zanardi; Maria Nobile; Sara Panseri; Enrica Ferretti; Sergio Ghidini; Stefano Foschini; Adriana Ianieri; Francesco Arioli (Food Additives & Contaminants: Part A, 2019)

Detection of glyphosate and its metabolites in food of animal origin based on ion-chromatography-high resolution mass spectrometry (IC-HRMS) - Luca Maria Chiesa; Maria Nobile; Sara Panseri; Francesco Arioli (Food Additives & Contaminants: Part A, 2019)

Risk characterisation from the presence of environmental contaminants and antibiotic residues in wild and farmed salmon from different FAO zones - Luca Maria Chiesa; Maria Nobile; Federica Ceriani; Renato Malandra; Francesco Arioli; Sara Panseri (Food Additives & Contaminants: Part A, 2019)

Evaluation of parabens and their metabolites in fish and fish products: a comprehensive analytical approach using LC-HRMS - Luca Maria Chiesa; Radmila Pavlovic; Sara Panseri; Francesco Arioli (Food Additives & Contaminants: Part A, 2018)

Levels and distribution of PBDEs and PFASs in pork from different European countries - Luca Maria Chiesa; Shih-Kuo Lin; Federica Ceriani; Sara Panseri; Francesco Arioli (Food Additives & Contaminants: Part A, 2018)

Distribution of POPs, pesticides and antibiotic residues in organic honeys from different production areas - Luca Maria Chiesa; Sara Panseri; Maria Nobile; Federica Ceriani; Francesco Arioli (Food Additives & Contaminants: Part A, 2018)

Food safety traits of mussels and clams: distribution of PCBs, PBDEs, OCPs, PAHs and PFASs in sample from different areas using HRMS-Orbitrap ® and modified QuEChERS extraction followed by GC-MS/MS - Luca Maria Chiesa; Maria Nobile; Renato Malandra; Davide Pessina; Sara Panseri; Giuseppe Federico Labella; Francesco Arioli (Food Additives & Contaminants: Part A, 2018)

Endogenous level of acetic acid in yellowfin tuna ( Thunnus albacares ): a pilot study about a possible controversy on its residue nature - Luca Maria Chiesa; Elisa Pasquale; Sara Panseri; Domenico Britti; Renato Malandra; Roberto Villa; Francesco Arioli (Food Additives & Contaminants: Part A, 2017)

Accelerated solvent extraction by using an ‘in-line’ clean-up approach for multiresidue analysis of pesticides in organic honey - Luca Maria Chiesa; Giuseppe Federico Labella; Sara Panseri; Domenico Britti; Fabrizio Galbiati; Roberto Villa; Francesco Arioli (Food Additives & Contaminants: Part A, 2017)

Bovine teeth as a novel matrix for the control of the food chain: liquid chromatography–tandem mass spectrometry detection of treatments with prednisolone, dexamethasone, estradiol, nandrolone and seven β 2 -agonists - Luca Maria Chiesa; Maria Nobile; Sara Panseri; Bartolomeo Biolatti; Francesca Tiziana Cannizzo; Radmila Pavlovic; Francesco Arioli (Food Additives & Contaminants: Part A, 2017)